Pengaruh Investasi dan Indeks Pembangunan Manusia Terhadap Produk Domestik Bruto di Indonesia 2015-2024 - Sri Ayu Ningsi; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of investment and the Human Development Index (HDI) on Indonesia’s Gross Domestic Product (GDP) during the period 2015–2024. Investment reflects capital accumulation, while HDI represents the quality of human resources, both of which are key drivers of economic growth. This research employs a quantitative approach using time series data obtained from Statistics Indonesia (BPS) and the Ministry of Investment. The analytical method used is multiple linear regression. The results indicate that investment has a positive and significant effect on GDP, while HDI also shows a positive and significant influence, highlighting the importance of improving human capital quality alongside capital formation to achieve sustainable economic growth in Indonesia.